In Search of Excellence: Convex versus Concave Noble Metal Nanostructures for Electrocatalytic Applications. Issue 13 (22nd February 2021) - Iqbal, Muhammad; Bando, Yoshio; Sun, Ziqi; Wu, Kevin C.‐W.; Rowan, Alan E.; Na, Jongbeom; Guan, Bu Yuan; Yamauchi, Yusuke
Abstract: Controlling the shape of noble metal nanoparticles is a challenging but important task in electrocatalysis. Apart from hollow and nanocage structures, concave noble metal nanoparticles are considered a new class of unconventional electrocatalysts that exhibit superior electrocatalytic properties as compared with those of conventional nanoparticles (including convex and flat ones). Herein, several facile and highly reproducible routes for synthesizing nanostructured concave noble metal materials reported in the literature are discussed, together with their advantages over noble metal nanoparticles with convex shapes. In addition, possible ways of optimizing the synthesis procedure and enhancing the electrocatalytic characteristics of concave metal nanoparticles are suggested. Nanostructured noble metals with concave features are found to show better catalytic activity and stability hence improve their practical applicability in electrocatalysis. Abstract : Concave noble metal nanocrystals represent the new class of electrocatalyst materials. In recent decades, extensive works have been employed in the search for excellent catalyst materials for electrocatalysis applications. The surface defects and structural stability are considered responsible for the superiority of concave noble metals compared to their conventional convex counterparts.